2018
DOI: 10.3389/fcvm.2018.00117
|View full text |Cite
|
Sign up to set email alerts
|

Dicarbonyl Stress and Glyoxalase-1 in Skeletal Muscle: Implications for Insulin Resistance and Type 2 Diabetes

Abstract: Glyoxalase-1 (GLO1) is a ubiquitously expressed cytosolic protein which plays a role in the natural maintenance of cellular health and is abundantly expressed in human skeletal muscle. A consequence of reduced GLO1 protein expression is cellular dicarbonyl stress, which is elevated in obesity, insulin resistance and type 2 diabetes (T2DM). Both in vitro and pre-clinical models suggest dicarbonyl stress per se induces insulin resistance and is prevented by GLO1 overexpression, implicating a potential role for G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 108 publications
1
19
0
Order By: Relevance
“…MGO administration in our study has been shown to induce severe dicarbonyl stress comparable to levels in T2D patients with poorly controlled diabetes. In our study, MGO aggravated glucose intolerance and increased insulin resistance in the tissues of hypertriglyceridaemic rats, corroborating previous findings [13]. Although MGO administration had no effect on ectopic lipid deposition or body weight in the current study, MGO-treated HHTg rats exhibited changes in blood lipid profiles as serum triglycerides were decreased and total serum cholesterol was significantly increased.…”
Section: Discussionsupporting
confidence: 92%
“…MGO administration in our study has been shown to induce severe dicarbonyl stress comparable to levels in T2D patients with poorly controlled diabetes. In our study, MGO aggravated glucose intolerance and increased insulin resistance in the tissues of hypertriglyceridaemic rats, corroborating previous findings [13]. Although MGO administration had no effect on ectopic lipid deposition or body weight in the current study, MGO-treated HHTg rats exhibited changes in blood lipid profiles as serum triglycerides were decreased and total serum cholesterol was significantly increased.…”
Section: Discussionsupporting
confidence: 92%
“… 17 Also, the expression of glyoxalase I (GLO1) was decreased in response to noise, indicating impaired detoxification of methylglyoxal and other reactive aldehydes and accordingly pointing to an altered defense against metabolic stress. 18 Finally, noise reduced the levels of ACE2, an enzyme attached to the outer cell membranes of cells in the lungs, arteries, heart, kidney, and intestines. ACE2 lowers blood pressure by removal of the vasoconstrictor angiotensin II and accordingly its down-regulation by noise will indirectly increase the blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…In this pathway, Glo-1, a major MG detoxifying enzyme, catalyzes the first and the rate-limiting step in the removal of MG, and is crucial in protecting cells against oxidative stress [ 18 , 19 ]. A lack of Glo-1 elicits damage to mitochondria due to increased ROS production [ 20 ]. The linkage between a lack of Glo-1 and ROS production, inflammation, and apoptosis has also been causatively demonstrated [ 5 , 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%